Students’ Perception toward Online Learning in Pandemic Situations in English Speaking Classrooms - Wahyutami Dewi; Imam Qalyubi; Aris Sugianto (Loquen, 2022)
This study was aimed to know the students’ perception of online learning on Public Speaking class during Covid-19 pandemic. This study was the qualitative descriptive approach. Three instruments were used to collect the data, those are: observations, interview, and documentation. The subject of this study were the second semester students of the English Education Study Program in IAIN Palangka Raya. Purposive sampling was used to determine them based on some criteria needed. The result of this research viewed that students enjoyed online learning during the Covid-19 pandemic because they feel happy that they can still learn even through online learning. In a pandemic situation, they find it helpful to have online learning through applications that make it easier for them to learn to speak, such as WhatsApp and Google meet. Their lecturer also explain the material well, making it easier for students to understand the material. However, some students considered that they were dissatisfied through online learning in speaking classes because they could not meet face to face when learning public speaking